Comparative evaluation of wind resources using the computer tool WAPs, case study of Mecheria West Algeria - F Amrani; I Missoum; B Bekkouche (Trends in Computer Science and Information Technology - Peertechz Publications, 2022)
The aim of this work is to assess the wind potential in the Mecheriaregion, located in Western Algerian Hautes plains that are characterized by an important elevation average between 800m and 1400m, which has a major impact on wind speed acceleration. Using ten years of collected data from 2011 to 2021, the statistical analysis gives an annual mean wind speed equal to 5.6 m/s at 10m hub height above the ground level. Then four main types of wind turbines: NEG-Micon 44/750 kW, Nordex N50/800 kW, Vestas V50/850 kW and PowerWind 56/900 kW. are compared and analyzed using WAsP software to obtain the annual wind characteristics A, k, V and P for each wind turbine and select the most appropriate technology in the study area. Furthermore, an economic analysis was carried out by RETScreen software, to select the turbine that produces low cost and high capacity factors, and the results show that PwerWind 56 turbine is the most suitable one for the selected site.